Pengaruh Kredit Non Perfoming Dan Loan To Debt Ratio Terhadap Profitabilitas Yang Dimoderasi Oleh Rasio Kecukupan Modal Pada Bank Ekonomi Rakyat - Armansyah Armansyah; Dedy Takdir Syaifuddin; Ummy Kalsum (STIE AMKOP, 2023)
This study is to determine and analyze the effect of Non Performing Loan on Profitability, the effect of Loan to Debt Ratio on Profitability, the effect of Non Performing Loan on Profitability moderated by Capital Adequacy Ratio and the effect of Loan to Debt Ratio on Profitability moderated by Capital Adequacy Ratio of BPR in Southeast Sulawesi. The population of this study is all rural banks in Southeast Sulawesi Province. a total of 17 BPR. Sample selection is carried out by purposive sampling method. Data analysis in this study uses the Path Analysis method using PLS software. The results showed that NPL has a negative and significant effect on profitability, LDR has a positive and significant effect on profitability, CAR plays a role in strengthening the influence of NPL on profitability although not significant and CAR plays a role in strengthening the influence of LDR on profitability (ROA, ROE and NIM) although not significant on BPR in Southeast Sulawesi Province. Keywords: NPL, LDR, CAR, Profitability